Integration of Ushul Fiqh and Syara’ Sources in Addressing Contemporary Legal Challenges: The Role of Fatwa Institutions and Guidelines for Mujtahids - Najra, Ainun; Subli, Mohamad; Selvia, Fivi; Nelfiani, Nelfiani (IAIN Bone, 2024)
Contemporary issues such as financial technology, biotechnology, and social change present new challenges in the establishment of Islamic law, necessitating an approach based on ushul fiqh. This study aims to analyze how ushul fiqh, through the integration of syara' sources (the Qur'an, Hadith, ijma', and qiyas), can be applied to address modern challenges and provide relevant, contextual legal guidance. Using a qualitative research method with a descriptive-analytical approach, primary data was gathered from foundational Islamic legal texts, while secondary data was obtained from classical literature, scholarly journals, and fatwas from official bodies like the National Sharia Council (DSN) and the Indonesian Ulema Council (MUI). The data was analyzed through reduction, classification, and interpretation techniques to answer the research questions. The study found that the principles of maqashid shariah (the preservation of religion, life, intellect, lineage, and wealth) play a crucial role in navigating contemporary issues. Fatwa institutions play a strategic role in transforming the theory of ushul fiqh into practical guidance through a collaborative and flexible approach, while mujtahids are expected to conduct ijtihad using an interdisciplinary and information technology-based approach to produce sound and applicable rulings. The study contributes theoretically by enriching the Islamic legal literature and practically by providing guidance for fatwa institutions and mujtahids to respond adaptively to the challenges of the times. The study’s implications indicate that Islamic law remains relevant for addressing the dynamics of modern society, provided that it is accompanied by a contextual and shariah-based approach.